-4(2x-6)=33

Simple and best practice solution for -4(2x-6)=33 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(2x-6)=33 equation:


Simplifying
-4(2x + -6) = 33

Reorder the terms:
-4(-6 + 2x) = 33
(-6 * -4 + 2x * -4) = 33
(24 + -8x) = 33

Solving
24 + -8x = 33

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-24' to each side of the equation.
24 + -24 + -8x = 33 + -24

Combine like terms: 24 + -24 = 0
0 + -8x = 33 + -24
-8x = 33 + -24

Combine like terms: 33 + -24 = 9
-8x = 9

Divide each side by '-8'.
x = -1.125

Simplifying
x = -1.125

See similar equations:

| 5x+7=15x-1 | | 2t^2+7t+5= | | m/19=56/133 | | x^4=0.7 | | x^4=7 | | 2u^2-11u+12= | | 2(y+3)=4(y+2) | | -3(2x-7)=28 | | 0.8-2x=(-3x) | | 3(x+2)=4(2-x) | | -10=9a+17 | | 16r=256 | | 7(1-x)=2(1-3x) | | 6x-3(5x+3)=17 | | (-2)-3+2= | | 0.08-0.2x=1.32 | | 42y+43+53=180 | | 0=x*x+7x+12 | | 14r=98 | | 3p^2+10p+7= | | 100+30+2y=180 | | h(x)=2x^2+3x+1 | | 2x-4=-4x+6 | | 4(3v-2)=8(2w+3) | | 3x+8=-x+12 | | 3y-11=-3 | | 65+73+7x=180 | | 2t^2+11t+9= | | M^2-6m-85=6 | | 2y^2+y+11=0 | | 76+68+3u=180 | | 3v^2+5v+2= |

Equations solver categories